DERMATOGLIFI UJUNG JARI DAN TELAPAK TANGAN PENDERITA HEMOFILIA DI SUMATERA BARAT - Masni, Rika Tirta (Pendidikan Biologi, 2014)
Dermatoglyphic has associated with many genetic disorder. Hemophilic is ressesive genetic disorder that linkage in Xchromosome. This study aimed to describe characteristic of fingerprints pattern, total ridge count, atd angle, andpalmprints pattern frequency of hemophilic patients in West Sumatera. The dermatoglyphic features of 20 hemophilicpatients and 20 control group were collected from April 2014 to June 2014 in DR. M. Djamil hospital and a few regionsin West Sumatera consist of Padang, Solok, Pariaman, West Pasaman, and South Pesisir. The data was analysed usingchi square test, t test, and percentage. From the analysis, Arch pattern was not found in hemophilic patients and RadialLoop pattern percentage was much than control (33%>28,5%). Average of total ridge count hemophilic patients wassmaller than control (164,25<185,4). Atd values were 30o-52o and 33o-70o for the hemophilic patients and control. Infact, the values were not significant different between hemophilic patients and control. But, palmprints patternfrequency have different which in hemophilic patiens were founded in hypothenar, interdigital III, and interdigital IV.Meanwhile, palmprints pattern frequency in control were founded in all of palm areas.